A note on the use of variational methods for treatment of plate dynamics - Grossi, Ricardo Oscar (2011)
The present note deals with a methodology for development of compact analytical schemes, for the derivation of boundary value problems, which describe the statical and dynamical behaviours of plates with complicating effects. A special set of multi-indices in differentiation symbols and two formulae of integration by parts are introduced to develop compact analytical expressions in the procedures for deriving the governing differential equations and natural boundary conditions.